THE INFLUENCE OF SOCIAL COST, FAMILY OWNERSHIP, CAPITAL STRUCTURE ON FIRM VALUE - Jessica Louie Honggono; Henryanto Wijaya (Graduate Program of Universitas Tarumanagara, 2024)
In the time span of 2020-2022, this study aims to collect empirical evidence related to the influence of social costs of family ownership and capital structure on company valuation in the mining sector on the Indonesia Stock Exchange (IDX). The sample consists of 30 data, selected by non-probability sampling method from companies that are continuously listed on the IDX during 2020 to 2022. Data processing is carried out using panel data techniques using Eviews 12 software. This study shows that social cost has a positive effect on firm value, family ownership has a positive and insignificant effect and capital structure has a negative and insignificant effect.